Growth factors and corneal epithelial wound healing - Yu, Fu-Shin X. (2009)
In this article, we briefly review recent findings in the effects of growth factors including the EGF family, KGF, HGF, IGF, insulin, and TGF-β on corneal epithelial wound healing. We discuss the essential role of EGFR in inter-receptor cross-talk in response to wounding in corneal epithelium and bring forward a concept of “alarmins” to the field of wound healing research.